Peningkatan Kemampuan Literasi, Kreativitas, dan Pengetahuan Siswa SMP Muhammadiyah Palangkaraya Melalui Lomba Mading: Increasing Literacy, Creativity, and Abilities Knowledge of Muhammadiyah Palangkaraya Middle School Students Through Mading Competition - Al Fadli, Rofi Azka; Lidiatanti, Anggita Ratih; Utami, Restin Trisna; Fatchurahman, M. (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Literacy culture is closely related to formal and informal education. Schools have a very important role in instilling a culture of reading and writing in students. Mading can be one way to increase the cultivation of literacy culture. This activity uses a participatory approach that requires the involvement of junior high school students Muhammadiyah Palangkaraya in holding a wall magazine competition. The results of this research are that students at Palangka Raya Muhammadiyah Middle School are enthusiastic about taking part in the existing media competitions, meaning that students need a lighter to be able to make media, which is expected to be the beginning of students' interest in the world of literacy. The main problem with the lack of running of the Mading at Palangka Raya Muhammadiyah Middle School is caused by the lack of motivation in managing the Mading at Palangka Raya Muhammadiyah Middle School, either from teachers or student organizations such as the IPM.